Iconocity Adaptation: An Analysis of Onomatopoeias in Finance Smurf Comic and Its Indonesian Translation Smurf Bendahara - Ailsa Agatha Santoso; Nina Setyaningsih (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2020)
Onomatopoeia is one example of iconic signs influenced by the culture of the origin of the speakers. Translating an onomatopoeic word will need more than just a dictionary, but also culture and linguistic understanding of both source and target languages. Dealing with this issue, this research attempts to investigate how the onomatopoeias featured in the Finance Smurfs comic is translated into Indonesian. The data were obtained from Finance Smurfs comic and its translated version. Using articulatory phonetics to describe 47 onomatopoeias found in the comic, 43 are classified as iconic in both SL and TL, while 4 of them are not iconic. In addition, although the forms of onomatopoeias in source and target language are different their meanings are maintained based on the context.